Early Stage Development of a Newcastle Disease Vaccine Candidate in Corn - Shahid, Naila (Front Vet Sci, 2020)
Newcastle disease (ND) is a viral disease that causes labored breathing, periorbital oedema, and ataxia in the majority of avian species. The available vaccines against Newcastle disease virus (NDV) are limited, owing to their low reactivity and multiple dosage requirements. Plant-based machinery provides an attractive and safe system for vaccine production. In the current study, we attempted to express fusion (F) and hemagglutinin-neuraminidase (HN) proteins (the protective antigens against NDV) under constitutive 35S and seed-specific Zein promoters, respectively. Almost 2–7.1-fold higher expression of F gene mRNA in transgenic corn leaves and 8–28-fold higher expression of HN gene mRNA in transgenic corn seeds were observed, when the expression was analyzed by real-time PCR on a relative basis as compared to non-transgenic control plant material (Leaves and seeds). Similarly, 1.66 μg/ml of F protein in corn leaves, i.e., 0.5% of total soluble protein, and 2.4 μg/ml of HN protein in corn seed, i.e., 0.8% of total seed protein, were found when calculated through ELISA. Similar levels of immunological response were generated in chicks immunized through injection of E. coli-produced pET F and pET HN protein as in chickens orally fed leaves and seeds of maize with expressed immunogenic protein. Moreover, the detection of anti-NDV antibodies in the sera of chickens that were fed maize with immunogenic protein, and the absence of these antibodies in chickens fed a normal diet, confirmed the specificity of the antibodies generated through feeding, and demonstrated the potential of utilizing plants for producing more vaccine doses, vaccine generation at higher levels and against other infectious diseases.